Current practices on infant feeding in rural areas of Assam, India: a community based cross sectional study - Kalita, Debadeep; Borah, Madhur (International Journal Of Community Medicine And Public Health, 2017)
Background: Understanding of current practices and factors influencing infant care and feeding is imperative to identify various barriers that influence newborn and infant health. The present study was undertaken with the objectives to study the current practices related to infant feeding in rural areas of Kamprup District of Assam state, India and to identify various factors influencing the feeding practices. Methods: It was a community based cross sectional study done among 380 mothers having children in the age group of 1 to 2 years. Predesigned and pretested semi structured questionnaire was used for the study and statistical analysis was done using appropriate softwares. Results: We found that 70.5% of mothers in our study initiated breast feeding within 1 hour of birth. Baby separation was found to be the commonest reason (45.05%) for delayed initiation of breastfeeding. Exclusive breast feeding for first six months was found to be 70.3%. Exclusive breast feeding was found to be significantly associated with 4 or more numbers of ANC visits, primipara mothers, higher educational status, younger age and lower socioeconomic status of the mothers. Conclusions: Major findings of the study includes high percentage of mothers initiating breast feeding within 1 hour of birth of the child and exclusive breast feeding for six or more months. At the conclusion we can say that most of the infant feeding practices were satisfactory in our study.